The Pupil’s P’s: An Alliterative Tool and Practical Framework for Managing Older Patients - Milton Louca; Peter Gonski (International Journal of Medical Students)
Geriatrics encompasses all specialties of medicine. Therefore, medical students must be aware of many factors during their geriatrics rotation. Herein, we distil our reflections from medical school into employment to create a practical framework using an novel alliteration in: The Pupil’s P’s. We acknowledge and complement existing mnemonics devices, which are largely based on diagnosis, to introduce medical students to major geriatric topics to assist management whilst they round on their patients – Peculiar Presentations, Psychological Pertubations, Peristaltic Products, Profound Pain, Polypharmacy, Pressure Sores, Physiological De-conditioning, Poor Perception, Partner Practitioners, Post-Hospital Plan, Palliative Care, and Parsimony. For students of geriatric medicine, The Pupil’s P’s literary device creates a succinct, educative tool with the added utility as a reference to generate the multi-factorial reasoning required to care for older patients. Ultimately, through our experience in aged care, we wish to convey the important lesson of holistic, patient-centered care to students . Accordingly, despite the numerous issues that may be encountered with older patients, we emphasize treating the patient holistically, and not the individual problems which may be discovered.